Олігополізація як глобальна тенденція інформаційної економічної системи - Попадинець, Олена Василівна (Миколаївський національний університет ім. В. О. Сухомлинського, 2016)
Актуальність дослідження обумовлена погрозливими тенденціями посилення ролі олігополій у вітчизняній та світовій економіці. В статті розглядаються об’єктивні причини олігополізації інформаційної економіки, що обумовлено трансформацією традиційних економічних законів та принципів. Інформаційна економіка розглядається як нове середовище взаємодії фірм, якому властиво масове використання ІКТ для опосередкування різних соціально-економічних взаємодій, зміна структури виробничих сил у бік зростання частки нематеріальних чинників, олігополізація високотехнологічних секторів економіки. Останнє відбувається через трансформацію базових економічних законів (позитивний ефект масштабу, прямий і непрямий мережевий ефект, різке скорочення ЖЦТ, закони Мура, Гілдера і Меткалфа) і втратою невеликими виробниками конкурентоспроможності через необхідність високих до виробничих витрат та потребу у залучення і критичної маси споживачів.

In the global and domestic economy appears a big threat to the competitive environment. In the last decades has increased the emergence of oligopolies it is a global trend information economic system. This is especially the case in high-tech industries. These industries operate on the principles of information Economics. The article considers the objective causes of oligopolies information economy. The author considers as the cause of this transformation of the traditional economic laws and principles in information Economics don’t work. Itself information economy is a new environment for the firms, which is characterized by the massive use of information and communication technologies for various socio-economic interactions. It changes the structure of production forces, namely the increased share of intangible factors and decreases the value material factors. Oligopolies in high-tech sectors of the economy associated with the changes of basic economic laws. It comes to a continuous positive scale effect, direct and indirect network effects, reducing sharp’s, the laws of Moore, Metcalfe and Guilder) and the loss of small manufacturers competitiveness due to high production costs and the need to attract a critical mass of consumers. Only the achievement of a significant number of buyers provides the seller (company) has sufficient revenues that cover the high pre-production costs. These costs have the status of permanent. When variable costs and marginal costs are insignificant in value. Small manufacturers have to achieve a critical mass of consumers to bond together. large firms often use a network of traps when transport the consumer to another provider is associated with high costs.
Тhe emergence of oligopolies it is a global trend information economic system
Keywords: олігополія; транснаціональна корпорація; інформаційна економіка; мережа; мережеві пастки; ефект масштабу; oligopoly; multinational corporations; information Economics; network traps; economies of scale